IMPLEMENTATION OF VERBAL AND NONVERBAL COMMUNICATION IN THE KHURUJ ACTIVITIES OF STUDENTS OF DAARUL MUKHLASIN ISLAMIC BOARDING SCHOOL, BATURUSA VILLAGE - Hafiz Rahmatullah Ripandi; Gustin; Pani Azfa (Prodi Jurnalistik Islam IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Communication plays an important role in da'wah activities, especially in khuruj activities, which emphasize conveying the da'wah message to the community. Preaching doesn't just involve speaking ability, but how someone can make a good impression with the message of the sermon so that it is accepted by the target audience. Therefore, in achieving the success of da'wah, both verbal and non-verbal communication are needed in its delivery. The objectives of this research include: to determine the implementation of verbal and non-verbal communication in the khuruj activities of students at Daarul Mukhlasin Islamic boarding school in Baturusa village, to determine the procedures for khuruj activities of students at Daarul Mukhlasin Islamic boarding school in Baturusa village, and to identify the supporting and inhibiting factors in the khuruj activities of students at Daarul Mukhlasin Islamic boarding school in Baturusa village. To explain the three research objectives above, the researcher used a descriptive qualitative research method where the data generated does not contain numbers, but rather data obtained thru observation, interviews, and documentation, resulting in descriptive data. In this study, the researcher used six informants consisting of Ustadz and students from the Daarul Mukhlasin Islamic boarding school in Baturusa village. The research findings indicate the implementation of verbal and non-verbal communication during the khuruj activity. Which means verbal communication is used more frequently. Because during the community's khuruj, the ustaz and santri interacted with each other both verbally and in writing. Meanwhile, the implementation of verbal communication is found in the good habits of students taught by the pesantren and practiced during khuruj activities, so these good habits contain a da'wah message that can be accepted by society.